Strategic Variations in Fitts’ Task: Comparison of Healthy Older Adults and Cognitively Impaired Patients - Poletti, Céline; Sleimen-Malkoun, Rita; Decker, Leslie Marion; Retornaz, Frédérique; Lemaire, Patrick; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2017)
The present study aimed at investigating how healthy older adults and cognitively impaired patients differ in a discrete Fitts’ aiming task. Four levels of task difficulty were used, resulting from the simultaneous manipulation of the size of the target and its distance from home position. We found that movement times followed Fitts’ law in both healthy older adults and cognitively impaired patients, with the latter being significantly slower and more affected by increased task difficulty. Moreover, correlation analyses suggests that lower information processing speed and deficits in executive functions are associated with decline of sensori-motor performance in Fitts’ task. Analyses of strategic variations showed that healthy older adults and cognitively impaired patients differed in strategy repertoire (which strategies they used), strategy distribution (i.e., how often they used each available strategy), and strategy execution (i.e., how quick they were with each available strategy). These findings further our understanding of how strategic variations used in a sensori-motor task are affected by cognitive impairment in older adults.